2014
DOI: 10.12788/jcso.0058
|View full text |Cite
|
Sign up to set email alerts
|

Palonosetron versus older 5-HT3 receptor antagonists for nausea prevention in patients receiving chemotherapy: a multistudy analysis

Abstract: Background-No clinical standard currently exists for the optimal management of nausea induced by emetogenic chemotherapy, particularly delayed nausea.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 30 publications
0
3
0
Order By: Relevance
“…Palonosetron is a newer congener of ondansetron with a longer half-life of around 40 hours and has not been associated with significant QT interval prolongation. 6 Dexamethasone is a steroidal anti-inflammatory agent that has a central antiemetic action through the activation of glucocorticoid receptor in nuclei tractus solitarius in medulla. It decreases levels of 5-HT3 in neural tissue and in the gut and is commonly used as an antiemetic agent in cancer chemotherapy and PONV.…”
Section: Materials a N D Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Palonosetron is a newer congener of ondansetron with a longer half-life of around 40 hours and has not been associated with significant QT interval prolongation. 6 Dexamethasone is a steroidal anti-inflammatory agent that has a central antiemetic action through the activation of glucocorticoid receptor in nuclei tractus solitarius in medulla. It decreases levels of 5-HT3 in neural tissue and in the gut and is commonly used as an antiemetic agent in cancer chemotherapy and PONV.…”
Section: Materials a N D Methodsmentioning
confidence: 99%
“…5 It has not been associated with significant QT interval prolongation, an effect observed with other 5-HT3 receptor antagonists. 6 Dexamethasone has a central antiemetic action through the activation of glucocorticoid receptor in nuclei tractus solitarius in medulla. Dexamethasone has low cost and prolonged biological half-life of 36-48 hours.…”
Section: Introductionmentioning
confidence: 99%
“…It appears that the serotonin 5-HT 3 receptor may not be of major importance in mediating nausea. In a retrospective multistudy analysis, Morrow et al [51] suggested that palonosetron may be more effective than the first-generation 5-HT 3 receptor antagonists in the prevention of nausea, but there was no statistically significant difference among the first-generation 5-HT 3 receptor antagonists and palonosetron in the prevention of nausea in the multistudy analysis. Saito et al [31] reported an improvement in 'no nausea' in the delayed and overall periods after HEC in patients who received palonosetron plus dexamethasone compared to patients receiving granisetron plus dexamethasone, but the magnitude of the control was low ( Table 3).…”
Section: Prevention and Treatment Of Nausea With Palonosetronmentioning
confidence: 98%